Transanal hemorrhoidal dearterialization (THD) for hemorrhoidal disease: An Italian single-institution 5-year experience analysis and updated literature review - Luigi Verre; Gaetano Gallo; Giulia Grassi; Edoardo Bussolin; Ludovico Carbone; Gianmario Edoardo Poto; Osvaldo Carpineto Samorani; Luigi Marano; Daniele Marrelli; Franco Roviello (Frontiers in Surgery, 2022)
BackgroundHemorrhoidal disease is a highly prevalent, chronic disorder that usually compromise patients' quality of life. Despite recent advances in pharmacologic and surgical therapeutic options, a clear treatment “gold standard” is lacking. Our aim is to analyze the outcomes following Transanal Hemorrhoidal Dearterialization (THD) procedure.MethodsPatients who failed conservative treatment and underwent THD Doppler between 2017 and 2021 were enrolled. Follow-up interviews (consisting of clinical examination, Visual Analog Scale for pain—VAS, Vaizey incontinence score, Hemorrhoid Severity Score) were administered 1 week, 2 weeks, 1 month and 6 months after surgery.ResultsForty-seven out of 75 patients were male, and the mean age was 50 (± 17.9) years. Hemorrhoids were classified as Goligher's degree II in 25 cases, III in 40 and IV, simple irreducible without ischemic changes, in 10. The mean operative time was 35 (28–60) minutes, and most procedures were performed with epidural anesthesia (80%). No intraoperative complications occurred, and 73 patients (97.3%) were discharged within post-operative day 1. Early post-operative pain and bleeding occurred in 37.3% and 8% of patients, respectively. No patients experienced anal incontinence and severe symptoms at 6 months after surgery. The overall success rate was 97.3%.ConclusionsTHD is safe and effective in hemorrhoidal disease at degree II if bleeding, III, and IV without ischemic changes, both as a first intervention and on recurrence. Physician and patient need to understand each other's expectations, weight the risks and benefits, and customize the treatment.